Inertial properties of a living population for the development of biofidelic headforms - Connor, T. A.; Colgan, N.; Stewart, M.; Ní Annaidh, A.; Gilchrist, M. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
The aim of this study is to create a new database of human head physical properties based on a living adult population that can be used to inform the development of future biofidelic headforms. Relationships between head circumference and mass, as well as head moments of inertia and mass, are sufficiently linear to provide simple yet accurate values for the mass and inertia properties of differently sized heads. Physical data regarding the dimensions, mass, moments of inertia and centre of gravity location for the heads of 56 living adults were obtained using a non-invasive method based on computed tomography-based finite element models. The computed tomography data showed good agreement with published cadaver data and significantly less variation. The data set presented in this article provides an important basis for more biofidelic future headform designs. The linear equations associated with this new primary data set relate head circumference to head mass and moments of inertia: Head Mass = 0.18 × Head Circumference - 6.08, where mass is in kg and circumference is in cm, while Ixx = 79.88 × Head Mass - 132.88, Iyy = 81.70 × Head Mass - 128.38 and Izz = 53.88 × Head Mass - 86.66, where I is the moment of inertia in kg/cm2 and mass is in kg. The X, Y and Z axes correspond to forward, lateral and vertical directions and the XZ plane corresponds to the mid-sagittal plane. These results represent the first published human head physical property data that are based on a living population, rather than cadaver data. These data are freely available to all and should serve to improve the biofidelity of standard headforms in terms of their mass and moments of inertia.